HUBUNGAN ORIENTASI PASAR, STRATEGI BERSAING, KEWIRAUSAHAAN KORPORASI DAN KINERJA PERUSAHAAN - Sri Hartini (EKUITAS (Jurnal Ekonomi dan Keuangan), 2013)
This study aims to explain the research gap in the relationship of market orientation on firm performance. To explain the gap, this study focused on the role of moderator variables, that are competitive strategy and corporate and entrepreneurship. Unit analysis in the study is Small Medium Entreprise (SMEs) in East Java. This study used 250 samples, but only 120 companies are responded. Hypothesis test by MRA analysis and sub-groups analysis. MRA analysis is used to test the moderating role corporate entrepreneurship on relationship market orientation on firm performance. The study found that higher corporate entrepreneurship increasing the influence of market orientation on firm performance. Sub-groups analysis is used to examine the role of the firms competitive strategy as moderated variables in the relationship of market orientation on firm performance. The study found that the influence of market orientation on firm performance will be different on each difference competitive strategy. The competitive strategy moderating the relationship market orientation on firm performance.